MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X MELALUI MODEL DISCOVERY LEARNING - Salis Walida Rahma; Fatriya Adamura; Hadi Suparno (CV. ADIBA AISHA AMIRA, 2025)
The discovery learning model is a learning approach that focuses on the activities of students during the learning process. By directly involving students in the learning process, they become more motivated to learn, which in turn enhances their learning outcomes. This study aims to improve the mathematics learning outcomes of Grade X students by applying the discovery learning model. The method used in this research is classroom action research conducted with the students of Grade X AKL 2 at SMKN 2 Madiun. The subjects in this study consisted of 33 students. The results of this research indicate an increase in the percentage of student mastery. In the pre-cycle, the number of students who achieved mastery was 45% (15 students); in the first cycle, this increased to 58% (19 students); and in the second cycle, there was a significant increase to 100% (33 students) achieving mastery. The improvement in learning outcomes is also reflected in the students' average scores.